Pengaruh Citra Merek, Harga Dan Kualitas Produk Terhadap Minat Beli Ulang Pada Merek Minuman Menantea - Sukmawati Jaya, Florence; Hasyim, Hasyim (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
This study aims to prove the relationship between brand image, price, and product quality with partial repurchase interest, then the relationship between brand image, price, and product quality simultaneously on repurchase interest in Menantea products. This type of research is causal associative research with a quantitative method approach; the sample is determined through a non-probability sampling method with a purposive sampling technique, while the number of samples is determined based on the formula according to Hair et al. (2010) with the formula n x 5 and obtained from 100 respondents who have purchased menantea beverage products and are domiciled in the Jakarta, Bogor, Depok, Tangerang, and Bekasi areas. The data analysis method uses multiple linear regression. The results of this study indicate that repurchase interest in Menantea beverage products is influenced by price and product quality, but brand image has not been able to influence repurchase interest. Thus, through the findings of this study, there can be an evaluation of menantea and, on an ongoing basis, the desire of customers to gain repurchase interest from supporting factors, namely brand image, price, and product quality.